2000
DOI: 10.1074/jbc.275.4.2733
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Activity Is Involved in the Regulation of Myoblast Differentiation through Myogenin Expression and Activity of Myogenic Factors

Abstract: To characterize the regulatory pathways involved in the inhibition of cell differentiation induced by the impairment of mitochondrial activity, we investigated the relationships occurring between organelle activity and myogenesis using an avian myoblast cell line (QM7). The inhibition of mitochondrial translation by chloramphenicol led to a potent block of myoblast differentiation. Carbonyl cyanide p-(trifluoromethoxy) phenylhydrazone and oligomycin, which affect the organelle at different levels, exerted a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
163
0
9

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(203 citation statements)
references
References 38 publications
20
163
0
9
Order By: Relevance
“…In contrast, chloramphenicol, a drug inducing the opposite influence to p43 by reducing mitochondrial protein synthesis, inhibits myoblast withdrawal from the cell cycle and their differentiation. In this study (Rochard et al 2000), we obtained good evidence that changes in ATP production were not involved in this myogenic influence. More interestingly, we found that myogenin expression was increased by p43 overexpression and decreased by chloramphenicol, events elicited at transcriptional level, thus establishing the existence of an actual regulation of myoblast differentiation by mitochondrial activity.…”
Section: Physiological Importance Of the Direct Mitochondrial T3 Pathwaysupporting
confidence: 52%
See 1 more Smart Citation
“…In contrast, chloramphenicol, a drug inducing the opposite influence to p43 by reducing mitochondrial protein synthesis, inhibits myoblast withdrawal from the cell cycle and their differentiation. In this study (Rochard et al 2000), we obtained good evidence that changes in ATP production were not involved in this myogenic influence. More interestingly, we found that myogenin expression was increased by p43 overexpression and decreased by chloramphenicol, events elicited at transcriptional level, thus establishing the existence of an actual regulation of myoblast differentiation by mitochondrial activity.…”
Section: Physiological Importance Of the Direct Mitochondrial T3 Pathwaysupporting
confidence: 52%
“…To clarify this point, we studied the influence of the direct mitochondrial T3 pathway on myoblast differentiation (Rochard et al 2000). First, T3 is a major regulator of myoblast differentiation (Marchal et al 1993), through mechanisms involving its c-Erb A nuclear receptors .…”
Section: Physiological Importance Of the Direct Mitochondrial T3 Pathwaymentioning
confidence: 99%
“…Besides, recent studies have shown that mitochondria play a prominent role in the regulation of skeletal myogenesis (Rochard et al, 2000;Wagatsuma and Sakuma, 2013). Increased mitochondrial mass, mitochondrial DNA (mtDNA) copy number and mitochondrial respiration have been observed during C2C12 myogenic differentiation (Remels et al, 2010), suggesting the increased mitochondrial function may be essential for skeletal myogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Increased mitochondrial mass, mitochondrial DNA (mtDNA) copy number and mitochondrial respiration have been observed during C2C12 myogenic differentiation (Remels et al, 2010), suggesting the increased mitochondrial function may be essential for skeletal myogenesis. Moreover, blocking mitochondrial biogenesis inhibits myogenic differentiation (Rochard et al, 2000). Our previous study using a pig model indicated that moderately increased maternal dietary energy intake delayed fetal skeletal muscle differentiation and maturity on day 90 of gestation through changing myogenic gene expression and muscle fiber characteristics (Zou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several of the identified genes were of mitochondrial origin, known to be involved in energy metabolism (Denver et al 1997). Recently, demonstration of the TH receptor in mitochondria and its involvement in controlling gene expression in mitochondria by different groups further potentiate the role of TH in energy metabolism (Hashizume & Ichikawa 1982, Wrutnaik et al 1995, Enriquez et al 1999, Rochard et al 2000. Establishment of the mitochondria's key role in apoptosis, a cardinal feature of neurogenesis, indicates that mitochondria may also play an important role in brain development (Oppenheim 1991, Yuan & Yanker 2000.…”
Section: Introductionmentioning
confidence: 99%